Repressive crackdown on Tunisian CSOs following months of escalating violence against migrants and refugees - Amnesty International (Amnesty International, 2024)
Tunisia’s authorities must immediately end this vicious campaign and halt all reprisals against NGO workers providing essential support, including shelter, to migrants and refugees.
Keywords: Freedom of Movement

Georgia: Dark day as parliament bulldozes adoption of repressive “foreign influence” bill - Amnesty International (Amnesty International, 2024)
This damaging bill contravenes Georgia’s international obligations on the rights to freedom of expression and association and strikes at the heart of the civil society’s ability to operate freely and effectively

Monde. Le nombre d’exécutions à son plus haut niveau en près d’une décennie Le nombre d’exécutions à son plus haut niveau en près d’une décennie - Amnesty International (Amnesty International, 2024)
En 2023 Amnesty a constaté une augmentation importante des exécutions à travers le Moyen-Orient.

New technology and AI used at borders increases inequalities and undermines human rights of migrants - Amnesty International (Amnesty International, 2024)
Global: New technology and AI used at borders increases inequalities and undermines human rights of migrants

Tunisie. Réfugié·e·s, migrant·e·s et organisations de la société civile sont visés par des opérations répressives après des mois d’escalade de la violence - Amnesty International (Amnesty International, 2024)
Au cours des deux dernières semaines, le gouvernement tunisien a mené une campagne répressive sans précédent contre les migrant·e·s, les réfugié·e·s et les défenseur·e·s des droits humains s’efforçant de protéger leurs droits, ainsi que contre des journalistes, a déclaré Amnesty International jeudi 16 mai.

Israel must comply with ICJ order to immediately halt military operations in Rafah - Amnesty International (Amnesty International, 2024)
The Israeli authorities must completely halt military operations in Rafah, as any ongoing military action could constitute an underlying act of genocide.

Las nuevas tecnologías y la inteligencia artificial utilizadas en la fronteras aumentan las desigualdades y socavan los derechos humanos de las personas migrantes - Amnesty International (Amnistía Internacional, 2024)
En un nuevo documento de investigación publicado hoy, Amnistía Internacional documenta ampliamente las maneras en que la tecnología contribuye a la creciente tendencia de violaciones de derechos humanos en las fronteras, e insta a los Estados a que pongan fin al uso de dichas tecnologías hasta que garanticen que no vulnera derechos humanos. El informe, […]

Jour sombre pour la Géorgie, alors que le Parlement fait passer en force le projet de loi répressif sur l’« influence étrangère » - Amnesty International (Amnesty International, 2024)
Le parti au pouvoir en Géorgie a passé en force cette loi délétère, qui piétine les droits fondamentaux de tous en Géorgie.

Les nouvelles technologies et l’IA utilisées aux frontières accroissent les inégalités et sapent les droits des personnes migrantes - Amnesty International (Amnesty International, 2024)
La protection des droits humains ne doit pas être sacrifiée sur l’autel du profit privé.

Executions soar to highest number in almost a decade - Amnesty International (Amnesty International, 2024)
2023 saw a sharp rise in executions across the Middle East.